2019
DOI: 10.1111/iju.14013
|View full text |Cite
|
Sign up to set email alerts
|

Protection from injury of organs adjacent to a renal tumor during percutaneous cryoablation

Abstract: Renal cryoablation has become accepted as treatment for small renal tumors as an alternative to surgery. However, parallel with the increase in the use of this therapy, there also has been increases in the number of reports of complications related to renal cryoablation. One potential complication is injury to important non-renal structures adjacent to the ablated renal tumor, such as the colon, duodenum, ureter, psoas muscle and so on. To prevent injury of adjacent organs, separating organs from the tumor is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 58 publications
(134 reference statements)
0
6
0
Order By: Relevance
“…The adult renal tumor has the highest incidence rate of RCC, followed by transitional cell carcinoma originating from the collecting system of the kidney, so the renal tumor is also known as RCC. The human body is most likely to develop RCC when it is over 50 years old [ 11 ]. Compared with the transperitoneal approach, the surgeon can reach the kidney faster through the retroperitoneal laparoscopic approach and hardly interfere with other organs in the abdominal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…The adult renal tumor has the highest incidence rate of RCC, followed by transitional cell carcinoma originating from the collecting system of the kidney, so the renal tumor is also known as RCC. The human body is most likely to develop RCC when it is over 50 years old [ 11 ]. Compared with the transperitoneal approach, the surgeon can reach the kidney faster through the retroperitoneal laparoscopic approach and hardly interfere with other organs in the abdominal cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Further, cryoablation of T 1b renal cell carcinomas caused frequent complications (grade II or worse) 37 , although fewer complications were seen in completely endophytic masses 60 . To reduce the rate of complications, several techniques such as hydro-, carbo-, and pneumo-dissection 61 , balloon dissection, and probe traction 62 have been proposed to minimize the impact of cryoablation on adjacent non-renal structures.…”
Section: Cryoablation For the Treatment Of Various Types Of Cancers I...mentioning
confidence: 99%
“…To avoid collateral damage, the desirable distance between the ablation zone and organs not receiving treatment is 2 cm or more [34,38]. Although normal saline or dextrose in water can be used for hydrodissection, a nonionic solution of dextrose in water is preferred over saline solution during RF ablation [34,38,43,44]. Addition of a small amount of an iodinated contrast medium is useful for increasing the attenuation of the fluid and improving differentiation between the hydrodissection area and adjacent organs, as well as for identifying hemorrhage [45] (Figs.…”
Section: Hydrodissectionmentioning
confidence: 99%
“…Pyeloperfusion is a technique used to protect the renal collection system and ureter from thermal damage during renal ablation. A ureteral stent should be placed prior to pyeloperfusion, with the distal end located in the renal pelvis and the proximal end directed outwards from the urethra and connected to a water bag containing sterile saline or 5% dextrose for perfusion [34,38,43,44,46,47]. No randomized prospective study has analyzed the effectiveness of pyeloperfusion; however, Dai et al reported a 10% rate of hydronephrosis or urinoma as major complications after RF ablation combined with pyeloperfusion [48].…”
Section: Ureteral Stent Placement and Pyeloperfusionmentioning
confidence: 99%